A policy trajectory analysis of the internationalisation of Chinese humanities and social sciences research (1978–2020) - Xu, X (Elsevier, 2021)
Since the Reform and Opening-up in 1978, science and technology research has long been regarded as an engine for China’s modernisation. Comparatively, humanities and social sciences (HSS) research has been overlooked in national policy for a long period. Although China’s science and technology research has gained global prominence, its HSS research remains less visible in the world. This article reviews the policy trajectory of internationalising Chinese HSS research from 1978 to 2020. It identifies changing and unchanged tensions along the policy trajectory, explores the dynamics between the internationalisation and indigenisation (‘Chinalisation’) of HSS, and reveals a hybridisation of ideological openness and vigilance in Chinese HSS research. Based on the examination of those tensions, this article discusses the shifted power paradigm in Chinese HSS, the connotation and challenges of ‘Chinalisation’, and the tensions between national policies, institutional implementation and individual practices.